Uniola paniculata (Poaceae, Chloridoideae, Unioliinae), new record for the flora of the Yucatan Peninsula, Mexico - Tovar-Montalvo, Daniel Alexis; Medina-Acevedo, Monserrat; García-Bielma, Miguel Angel; Guerra-Santos, Jesús Jaime (Instituto de Ecología, A.C., 2020)
Background and Aims: The oat sea grass, Uniola paniculata, is distributed in the Caribbean, the United States of America and Mexico. The aim of this work is to report its occurrence and record in the state of Campeche, Mexico. Methods: Individuals of the family Poaceae were collected growing in a coastal dune in the southwest of the state of Campeche, particularly on the Isla del Carmen. The collections were processed and herborized for their conservation and classification. Key results: With the individuals’ identification and after reviewing its distribution, this is the first report of the presence of Uniola paniculata (Poaceae) on the Yucatan Peninsula, representing a contribution to the floristic knowledge of the region and the flora of Mexico. Conclusions: This species had only been reported from the coast of the Gulf of Mexico in the states of Tamaulipas, Veracruz and Tabasco. This record is relevant because of the ecological role of this oat sea grass in the coastal dunes.